Research on Failure Precursor Based on Characteristics of Energy Dissipation Rate for Rock - Liu, Xiaohui; Xue, Yang; Zheng, Yu; Li, Hongying (Frontiers in Earth Science, 2022)
Research on early warning of rock disaster based on the energy theory is closer to the essence of rock failure. In this paper, static compression tests and acoustic emission (AE) tests of coal rock under 0, 8, 16, and 25 MPa confining pressures were carried out on the MTS815 test system. Energy evolution law in the rock failure process was analyzed according to the relationship between mechanical parameters, AE parameters, and energy dissipation rate (EDR) in the rock failure process. Eventually, a new index for evaluating rock failure precursors was proposed based on EDR. The results show that the EDR has a good correlation with mechanical strength and AE events under different confining pressures. The deformation and failure characteristics of coal rock can be truly characterized by EDR. The variation of EDR can be divided into a quiet stage, a stable increasing stage, an active stage, and a stable stage. The EDR level in the quiet stage is obviously enhanced by confining pressure. When EDR reaches the peak, AE events increase rapidly. In the active stage, the EDR peak value is concentrated and large, the AE event is highly active, and stress drops abruptly, indicating that the EDR is reliable for evaluating the rock failure process. Compared with AE test results, it is found that the warning stress and warning time of the EDR failure precursor occur later than that of the AE failure precursor, and the former is closer to the peak stress of rock, which is more universal in engineering and could provide a better reference value for preventing rock disaster.